Implementation of drug counselling at Bakti Timah Hospital in Pangkalpinang City - Rachmawati Felani Djuria (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
Several studies have shown that the implementation of pharmaceutical services in the Bangka Belitung Islands Province has not been maximized, especially clinical pharmacy services. The results of other studies also showed that research on the quality of pharmaceutical services in clinical pharmacy service activities in full had never been carried out. Drug counseling is a form of clinical pharmacy service. Effective counseling requires patient and / or family trust in the pharmacist. This type of research is descriptive with a qualitative approach using concurrent observational research designs. Evaluation quality control methods used are by audit (supervision). The study was conducted at the Bakti Timah Hospital in Pangkalpinang City in February-December 2017. This study used key informants with the method of data collection by source triangulation and univariate analysis. The results showed that the activities of the pharmacy services of drug counseling clinics were carried out, but not optimally. The conclusion is that the implementation of drug counseling at the Bakti Timah Hospital in Pangkalpinang City is not in accordance with the Pharmaceutical Service Standards at the 2016 Hospital.